(untitled) (Central Asian Journal of Medical Sciences, 2025)
Objective: Our study aims to ascertain the types of information sources that shape adolescents’ knowledge about sexual and reproductive health in Mongolia. Methods: The present study, in accordance with the HBSC survey protocol, encompassed a sample of 312 students aged between 15 and 18 years in Ulaanbaatar and its metropolitan areas. Data collection occurred in a paper-based form. Besides descriptive statistics, logistic regression analyses were conducted. Results: The most prevalent sources of sexual health information were school health curricula (74.0%), friends (70.7%), and peers (65.6%), while less frequent sources included sexual partners (19.6%) and religious organizations (11.9%). Logistic regression analysis revealed that gender significantly influenced source preferences: females were more likely than males to seek information from parents, teachers, and health education curricula, while males were more likely to rely on sexual partners and friends. Conclusion: The findings indicated that the majority of participants received sexual health information through health education curricula, demonstrating the importance of these programs. Additionally, in light of the significant influence of peers and social media on adolescents, it is imperative to ensure they have access to reliable sexual health information through accessible sources and increased parental involvement to promote informed and responsible decision-making.